2023
DOI: 10.3389/fpubh.2023.1165107
|View full text |Cite
|
Sign up to set email alerts
|

HPV-related oropharyngeal cancer early detection in gay and bisexual men is an “orphan” practice: A qualitative analysis among healthcare providers

Abstract: IntroductionAmong US men, oropharyngeal cancer (cancer of the back of the mouth and throat) is the 8th most common cancer. If detected early, human papillomavirus (HPV)-16-associated oropharyngeal cancer has a high 5-year survival rate. Risk factors such as high numbers of oral sex partners, disparities in smoking and drinking, and low rates of HPV vaccination may put gay and bisexual men at even higher risk for oropharyngeal cancer.MethodsWe recruited 21 healthcare providers in Minneapolis-St. Paul, Minnesota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…However, recent previous research with practitioners ( 16 ) has indicated that clinical screening for OPSCC in the US is an “orphan” practice, with physicians infrequently screening GBM for OPSCC unless symptoms are reported, while dentists may limit their inspection to the oral cavity but not the oropharynx. This is despite practitioners with significant numbers of GBM patients being aware of the heightened risk of HPV-associated OPSCC in GBM.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent previous research with practitioners ( 16 ) has indicated that clinical screening for OPSCC in the US is an “orphan” practice, with physicians infrequently screening GBM for OPSCC unless symptoms are reported, while dentists may limit their inspection to the oral cavity but not the oropharynx. This is despite practitioners with significant numbers of GBM patients being aware of the heightened risk of HPV-associated OPSCC in GBM.…”
Section: Introductionmentioning
confidence: 99%